Viability and growth of feline preantral follicles in vitro cultured with insulin growth factor and epidermal growth factor supplemented medium - Alves, A. E.; Padilha-Nakaghi, L. C. [UNESP]; Pires-Butler, E. A. [UNESP]; Apparicio, M.; Silva, N. A.M.; Motheo, T. F. [UNESP]; Vicente, W. R.R. [UNESP]; Luvoni, G. C. (Wiley, 2017)
In vitro culture of ovarian preantral follicles has emerged as a reproductive technology aimed at obtaining large amount of oocytes for in vitro embryo production. The addition of growth factors (GF) in the in vitro culture of preantral follicles of different species has provided superior results of follicular development, antrum formation and proliferation of granulosa cells. However, there are only few reports regarding the use of these factors on feline preantral follicle in vitro culture. Thus, the aim of this study was to investigate the effect of a combination of IGF-1 and EGF on in vitro viability and growth of preantral follicles and enclosed oocytes collected from domestic cats. A total of 64 follicles characterized by multilayer granulosa cells were isolated and individually cultured for 6 days (T6) in minimum essential medium supplemented with IGF-1+ EGF (100 ng/ml each) or without (control). A higher percentage of follicles were viable after culture with GF than without, and an increase in size when IGF-1+ EGF were added to the medium (170 ± 32.4 μm (T0) vs. 201 ± 22.3 μm (T6); p <.05) was observed. An increase in the diameter was also observed in follicles cultured without GF, but this increase was only 8.3% compared to 15.4% of those cultured with GF (p <.05). No differences were found in the diameter of oocytes contained in follicles cultured in the non-supplemented or supplemented media (107.9 ± 11.8 μm (T0) vs. 113.2 ± 15.6 μm (T6); p >.05). These data suggest that the addition of IGF-1 and EGF to the culture medium promotes the in vitro development of preantral follicles of cats.
Keywords: cat; follicles; in vitro development